When digital-AI transformation sparks adaptation: job crafting and AI knowledge in job insecurity contexts - Sha, Chengcheng; Chai, Tianlong (Frontiers in Psychology, 2025)
IntroductionAs AI technology continues to rise, numerous studies have explored its impact on employee behavior. However, little is known about employees’ responses to the integration of AI in the digital transformation process. Drawing on Conservation of Resources Theory, this study aims to examine the impact of digital-AI transformation on employees’ job crafting behaviors, focusing on the mediating role of job insecurity and the moderating effect of AI knowledge.MethodsA two-wave survey was conducted among 400 employees actively using AI tools in digitally transforming organizations, resulting in 370 valid responses. Data were analyzed using SPSS 22.0 and the PROCESS macro (version 3.3) to test the proposed hypotheses.ResultsThe results indicate that digital-AI transformation has a significant positive effect on employees’ job crafting (β = 0.512, p < 0.001), with job insecurity serving as a mediator in this relationship (β = 0.228, p < 0.001). Employees’ AI knowledge not only moderates the positive effect of digital-AI transformation on job crafting (β = 0.060, p < 0.05), but also moderates the mediating role of job insecurity in the relationship between digital-AI transformation and job crafting (β = 0.143, p < 0.001).DiscussionThis study extends the application of Conservation of Resources Theory by emphasizing the potentially positive role of job insecurity under specific contextual conditions, while also offering a critical reflection on the ethical implications of using job insecurity as a motivational tool. It is suggested that organizations should leverage employees’ AI knowledge to enhance job crafting, rather than relying on stress as a driver. Future research is encouraged to explore additional antecedents of job crafting.